2021
DOI: 10.46827/ejmms.v7i1.1173
|View full text |Cite
|
Sign up to set email alerts
|

Are Women Entrepreneurs’ Business Performances Influenced by Financial Resources? Empowering Women Entrepreneurs in Malaysia Through Financial Resources Post-Covid-19 Pandemic

Abstract: Entrepreneurship has always been women's interest, and women have risen in the business arena. On the other hand, statistic shows that Malaysian women's participation in entrepreneurship is still minute but vital to Malaysia's economic development, as indicated by previous researchers. Additionally, the impact of the Covid-19 pandemic has caused adverse effects on women-owned businesses in Malaysia. This research aims to offer an insight into how financial capital, the amount of capital needed, and personal sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 41 publications
(82 reference statements)
0
8
0
Order By: Relevance
“…It was established that pricing strategy and decisions have a significant effect on sales performance. Kanapathipillai et al (2021) and (Louter et al, 1991) in their research revealed that there was a positive relationship between pricing strategy and firm performance.…”
Section: The Relationship Between Price and Sales Performancementioning
confidence: 92%
See 2 more Smart Citations
“…It was established that pricing strategy and decisions have a significant effect on sales performance. Kanapathipillai et al (2021) and (Louter et al, 1991) in their research revealed that there was a positive relationship between pricing strategy and firm performance.…”
Section: The Relationship Between Price and Sales Performancementioning
confidence: 92%
“…Mohammad (2015), in the research of 7ps marketing mix and retail bank customer satisfaction in northeast Nigeria, found that place is not significantly related to customer satisfaction and thus does not impact sales performance. Financial service providers are not seen as being very trustworthy, according to (Kanapathipillai et al, 2021;Cox, 2007). This is due to the complexity of the insurance services, as well as the increase in regulatory environment efficiency and competitiveness.…”
Section: Research Problem Statementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether they have been operating successfully for a long time or have high profits, they can afford costly conventional marketing channels such as television, radio, and billboards. On the other hand, small businesses lack the financial resources to conduct extensive marketing campaigns (Sivapatham et al, 2022;Kanapathipillai et al, 2021). Therefore, it is difficult for them to build brand awareness if they invest in costly advertisements or marketing strategies.…”
Section: Research Problem Statementmentioning
confidence: 99%
“…Even though social media platforms generate much interest among users, the topic is still relatively new, and research is constantly developing and expanding. According to (Kanapathipillai et al, 2021;Ismail, 2017), large companies have more significant financial resources to improve and achieve high brand awareness among consumers in a competitive market. Whether they have been in business for a long time or have high profits, they can afford expensive traditional marketing channels such as television, radio, and billboards (Farook et al, 2016).…”
Section: Relationship Between Brand Awareness and Effectiveness Of So...mentioning
confidence: 99%